2014
DOI: 10.1002/anie.201400837
|View full text |Cite
|
Sign up to set email alerts
|

Computational Ligand Design for the Reductive Elimination of ArCF3 from a Small Bite Angle PdII Complex: Remarkable Effect of a Perfluoroalkyl Phosphine

Abstract: To date only three ligands are known to trigger the challenging reductive elimination of ArCF3 from Pd(II). We report the computational design of a bidentate trifluoromethylphosphine ligand that although exhibiting a generally ineffective small bite angle is predicted to give facile reductive elimination. Our experimental verification gave quantitative formation of ArCF3 at 80 °C within 2 h. This highlights the distinct effect of P-CF3 in organometallic reactivity and constitutes a proof-of-principle study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 75 publications
3
83
0
1
Order By: Relevance
“…240 In 2014, Schoenebeck and co-workers showed that by increasing the electrostatic repulsion from the ligand toward the aryl and CF 3 groups on Pd, while decreasing the size of substituents that would otherwise destabilize the transition state, the first small bite-angled ligand to trigger the reductive elimination was computationally designed and experimentally verified ( Figure 13). 241 Additionally, kinetic measurements (ΔH ‡ = 27.9 ± 1.6 kcal/mol) were in good agreement with computational predictions.…”
Section: Aryl Trifluoromethylationsupporting
confidence: 63%
“…240 In 2014, Schoenebeck and co-workers showed that by increasing the electrostatic repulsion from the ligand toward the aryl and CF 3 groups on Pd, while decreasing the size of substituents that would otherwise destabilize the transition state, the first small bite-angled ligand to trigger the reductive elimination was computationally designed and experimentally verified ( Figure 13). 241 Additionally, kinetic measurements (ΔH ‡ = 27.9 ± 1.6 kcal/mol) were in good agreement with computational predictions.…”
Section: Aryl Trifluoromethylationsupporting
confidence: 63%
“…These signals are accompanied by selenium satellites ( 77 Se, 7.58% I = 1/2) from which | 1 J (PSe)| values ranging from ca. SevPPh 3 , 729 Hz, 20 SevP(iPr) 3 , 678 Hz 23 ) and those of phosphites (e.g. A comparison of these values with those reported for other phosphines is shown in Table 2.…”
Section: Oxidation Studiesmentioning
confidence: 85%
“…The first perfluoropropenyl ( pfp) containing phosphine was reported in 1969 in a Russian patent describing the preparation of (CF 3 ) 2 CvCFPR 2 (R = iPr, nBu) and (CF 3 )CFvCFP(nBu) 2 by reaction of lithium phosphides with perfluoroalkenes. Interestingly, in that work, it was also reported that the perfluoropropenyl-containing phosphines could not be oxidised to form the P(V) oxides or sulfides under standard conditions, although reaction with SF 4 did yield R 2 P(F) 2 CFvCF(CF 3 ). In the dark the trans-isomer was the favoured product (95%) while under UV photolysis conditions a somewhat lower yield of the trans-isomer (70%) was detected.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As part of our ongoing mechanistic and methodological program [11] that also focusses on the generation of fluorinecontaining compounds, [12] we recently developed metal-catalyzed C À SCF 3 bond formation protocols of aryl (pseudo)-halides,u sing the bench-stable "SCF 3 À "s ource (Me 4 N)SCF 3 . [13,14] During these investigations,w ee ncountered the unexpected formation of ac hallenging class of compounds,t hat is,athiocarbamoyl fluoride.T he subjection of one equivalent of (Me 4 N)SCF 3 to N-methylaniline in toluene at room temperature remarkably gave rise to facile and quantitative formation of N-methyl-N-phenylthiocarbamoyl fluoride 1a within minutes without any need for additional reagents or catalysts (see Scheme 1).…”
mentioning
confidence: 99%